Integrated Lean Operational Model to Increase Efficiency in a Winery Company - Carbajal-Macedo, Jassir V.; Serrano-Rossado, Gabriel N.; Chavez-Ugaz, Rafael; Leon-Chavarri, Claudia C. (LACCEI, 2025)
The pisco industry plays a key economic and cultural role in Peru. This study develops an operational model for the small Peruvian winery, dedicated to pisco production, with the objective of reducing the end-of-line cycle time through the application of Lean Manufacturing tools. The model comprises two integrated components: first, the stabilization of operations in the quality control and labeling stations through the application of 5S; and second, the physical redesign of critical activities using Poka Yoke and Slotting to improve workflow and reduce human error. Validation was conducted using a hybrid approach combining a pilot test and discrete-event simulation in Arena. The simulation demonstrated a 31.8% reduction in end-of-line time from 48.97 to 33.40 seconds per bottle, a 20% decrease in material search time, and a 76% reduction in the deviation of quality defects. These results suggest the effectiveness of the proposed solution in improving operational efficiency and highlight its potential for replication across other micro and small wineries in Peru’s wine sector.